Effect of Treatment of Subclinical Thyroid Dysfunction on Pregnancy Outcome in Patients with 1st Trimester Recurrent Miscarriages - Ambar Riaz, Maryam Rana, Asma Mushtaq, Umair Riaz Ahmad, Shayan Rashid Khawaja, Awais Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Thyroid dysfunction and thyroid autoimmunity are prevalent among women of reproductive age and are associated with adverse outcomes including miscarriage and preterm delivery. Preconception or early pregnancy screening for thyroid dysfunction has been proposed but is not widely accepted Objective: To determine the effect of treatment of subclinical thyroid dysfunction on pregnancy outcome(pregnancy going beyond 24 weeks ;period of viability in developing world/ miscarriage in first trimester) in patients with recurrent 1st trimester miscarriages. Material and Mathod: Study Design: Randomized controlled trial Settings: Department of Obstetric and Gynaecology, Lady Wallingdon Hospital, Lahore Duration: One year after submission of synopsis. Data Collection: The data was collected from the patients admitted in gynae unit 2 through outpatient department with history, examination and investigation which was included according to the inclusion criteria mentioned above. All the patients were assessed with thyroid hormone level. TSH and free T4 was sent to in pathology lab, the result was interpreted by the pathologist to evaluate for the presence of subclinical thyroid dysfunction according to operational definitions. The women with subclinical thyroid dysfunction was categorized as subclinical hypothyroidism and subclinical hyperthyroidism according to results. These women were further evaluated by endocrinologist to allocate them between treatment and control groups. The data collection procedure will be explained to each patient and informed written consent was taken . Each woman was ensured that confidentiality of each subject is kept. It is the matter of controversary in subject of gynecology whether to treat the subclinical thyroid dysfunction or not during pregnancy on the basis of which control group was selected. However if during research study convincing evidence comes in favour of giving treatment to control group then treatment was offered to those patient as well. Single blinding was maintained in control group by giving placebo therapy. Eligible women were allocated in 1:1 in treatment and control groups. The thyroxin (dose 0.5mg/kg body weight) was given to women with subclinical hypothyroidism in treatment group and propylthiouracil (0.3mg/kg body weight) was given to women with subclinical hyperthyroidism in treatment group to maintain TSH (0.45 to4.5IU) and the free t4 level between (14-20umol/l).woman thyroid function test was carried out on biweekly basis in follow up and dose adjustment accordingly. In non-treatment group no treatment given for subclinical thyroid dysfunction and outcomes was assessed and compared in both groups in current pregnancy in respect of miscarriage in first trimester or continuation of pregnancy beyond period of viability. Results: Frequency of miscarriage in treatment group and in control group was 60.2% and 78.5%. However frequency of miscarriage was significantly higher in control group as that of treatment group. There were 37(39.85) women in treatment group and 20(21.5%) women in control group in which continuation of pregnancy was seen beyond 24 weeks. However women in treatment group had high pregnancy continuation rate as that of control group. i.e. p-value=0.007 Conclusion: Results of this study showed that treatment of subclinical thyroid dysfunction during pregnancy in women with 1st trimester recurrent miscarriages has better pregnancy outcomes. Treatment of thyroid insufficiency during pregnancy is important in avoiding hostile not only maternal as well as fetal outcome